Construal Theory: A Review and Future Prospects - Ziwen Meng (Winaya Inspirasi Nusantara Foundation, 2025)
Background of the problem: Construal refers to human’s cognitive ability of using different perspectives and ways to view and describe the same situation. Purpose: This study aims to review the application of construal theory to see potential prospects. Method: This study uses a narrative review research design. The literature used as data in this study is scientific literature published indexed in various databases such as Google Scholar, Scopus, PubMed, and WOS. The data were synthesized and analyzed based on their relevance to the research topics. Result: Many scholars have defined the concept of construal from several angles and explained it from different dimensions. As a theoretical concept with high significance in Cognitive Grammar, construal also plays an irreplaceable role in meaning understanding. Implication: This paper introduces the current situation of the study of construal in three parts: from image to construal, the main branches and dimensions of construal, and the subjectivity and objectivity of construal.